Methodological substantiation of the choice for optimal modes of equipment operation during the stage-wise concentrate removal in iron ores beneficiation - Alexandr S. Opalev; Svetlana A. Alekseeva (Записки Горного института, 2022)
The urgent task of improving the quality of iron ore concentrates was studied. We propose to use the stage-wise removal of the concentrate by combining fine screening, regrinding, and magnetic-gravity separation. Exemplified by magnetite ore from the Stoilensky GOK, a scientific and methodological approach to the search for optimal separation parameters and modes was substantiated. It includes several stages: studying the particle size distribution and release of useful components in the feed product to select classification parameters; a series of experiments on grinding oversize products to diverse sizes; beneficiation of the obtained products by MG separation. To select the optimal parameters of ore preparation, an analysis of the beneficiation efficiency was used, which is calculated according to the Hancock – Luyken criterion. The results of the research are experimental dependences that connect the process parameters of beneficiation with those of fine vibratory screening. For the studied ferruginous quartzite ore processed at the Stoilensky GOK, the obtained dependences can be described by a second-order polynomial with a high accuracy of approximation. The best performance is achieved with a particle size of 0.1 mm: Fetot content in the concentrate is 69.7 %, recovery is 85 %, classification efficiency is 80.4 %. The top size of the product in this case is 0.076 mm, which corresponds to 70-73 % grinding size of –0.045 class.